Insecticide resistance status in Anopheles gambiae in southern Benin - PADONOIU, Germain Gil (My University, 2010)
Background: The emergence of pyrethroid resistance in Anopheles gambiae has become a serious concern to the future success of malaria control. In Benin, the National Malaria Control Programme has recently planned to scaling up long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) for malaria prevention. It is, therefore, crucial to monitor the level and type of insecticide resistance in An. gambiae, particularly in southern Benin where reduced efficacy of insecticide-treated nets (ITNs) and IRS has previously been reported. Methods: The protocol was based on mosquito collection during both dry and rainy seasons across forty districts selected in southern Benin. Bioassay were performed on adults collected from the field to assess the susceptibility of malaria vectors to insecticide-impregnated papers (permethrin 0.75%, delthamethrin 0.05%, DDT 4%, and bendiocarb 0.1%) following WHOPES guidelines. The species within An. gambiae complex, molecular form and presence of kdr and ace-1 mutations were determined by PCR. Results: Strong resistance to permethrin and DDT was found in An. gambiae populations from southern Benin, except in Aglangandan where mosquitoes were fully susceptible (mortality 100%) to all insecticides tested. PCR showed the presence of two sub-species of An. gambiae, namely An. gambiae s.s, and Anopheles melas, with a predominance for An. gambiae s.s (98%). The molecular M form of An. gambiae was predominant in southern Benin (97%). The kdr mutation was detected in all districts at various frequency (1% to 95%) whereas the Ace-1 mutation was found at a very low frequency (≤ 5%). Conclusion: This study showed a widespread resistance to permethrin in An. gambiae populations from southern Benin, with a significant increase of kdr frequency compared to what was observed previously in Benin. The low frequency of Ace-1 recorded in all populations is encouraging for the use of bendiocarb as an alternative insecticide to pyrethroids for IRS in Benin.
Keywords: Insecticide resistance; Anopheles gambiae; Southern Benin; Malaria.